Implementation of boolean algebraic structure and its decision making approach over lattice ordered multisets - Ilamathi V.S., Anusuya; J., Vimala (International Journal of Engineering and Technology, 2017)
A multiset is a collection of objects in which they are allowed to repeat. The purpose of this paper is to generalize the notion of Boolean algebra in the context of multisets. Furthermore, we consider 0 and 1 as multiset depiction and identify their role in Boolean algebra over lattice ordered multisets(dual), where some sorting exists among the parameters are explored.